2020
DOI: 10.1021/acs.jpcb.0c07620
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Excited Fluorescence Dynamics in NADH in Water–Methanol Solutions: The Role of Conformation States

Abstract: The dynamics of polarized fluorescence in reduced nicotinamide adenine dinucleotide (NADH) at 460 nm under two-photon excitation at 720 nm by femtosecond laser pulses in water−methanol solutions has been studied experimentally and theoretically as a function of methanol concentration. A number of fluorescence parameters have been determined from experiment by means of the global fit procedure and then compared with the results reported by other authors. A comprehensive analysis of experimental errors was made.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(93 citation statements)
references
References 59 publications
9
81
0
1
Order By: Relevance
“…We compare pressure cycling results with the piezochromic response of NADH solutions. Figure 3 shows spectra from NADH in solutions of varying polarity; methanol (from 0 to 90 vol%) instead of ethanol is used to vary the polarity due to the availability of previous studies on excited-state dynamics in water–methanol mixtures, which indicate an opening of the molecular conformation with increasing methanol [ 35 , 36 , 37 ]. We observe an increase in intensity and a shift to shorter emission wavelength as the methanol concentration is increased.…”
Section: Resultsmentioning
confidence: 99%
“…We compare pressure cycling results with the piezochromic response of NADH solutions. Figure 3 shows spectra from NADH in solutions of varying polarity; methanol (from 0 to 90 vol%) instead of ethanol is used to vary the polarity due to the availability of previous studies on excited-state dynamics in water–methanol mixtures, which indicate an opening of the molecular conformation with increasing methanol [ 35 , 36 , 37 ]. We observe an increase in intensity and a shift to shorter emission wavelength as the methanol concentration is increased.…”
Section: Resultsmentioning
confidence: 99%
“…Быстрые релаксационные процессы, происходящие в возбужденных состояниях многоатомных молекул в растворах и живых клетках, очень часто являются анизотропными, обычно они исследуются методами многофотонной поляризованной флуоресценции [7][8][9][10][11][12] или методами поляризационной спектроскопии pumpprobe [13][14][15][16][17][18][19][20][21]. В обоих случаях линейно поляризованный лазерный импульс фемтосекундной длительности переводит исследуемые молекулы в возбужденное электронное состояние, причем образующийся ансамбль возбужденных молекул, как правило, характеризуется выстраиванием по направлениям молекулярных осей.…”
Section: Introductionunclassified
“…Numerous time-resolved fluorescence studies carried out in solutions, cells, and living tissues revealed that after excitation in the first absorption band at 320-370 nm related to the nicotinamide (NA) chromophore group NADH exhibits a multicomponent decay dynamics. In aqueous solution free NADH is known to exhibit biexponential fluorescence decay with the lifetimes of about 0.3 ns and 0.7 ns [14,15,16,17,18,19,20]. In other solvents the lifetimes and corresponding weighting coefficients depend strongly on temperature and solvent type [21,15,14,17,20].…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution free NADH is known to exhibit biexponential fluorescence decay with the lifetimes of about 0.3 ns and 0.7 ns [14,15,16,17,18,19,20]. In other solvents the lifetimes and corresponding weighting coefficients depend strongly on temperature and solvent type [21,15,14,17,20]. At the same time in enzyme-containing solutions and in cells it is most common to fit NADH fluorescence decay in the nanosecond time domain by two exponentials, one of them having the decay times of several ns and another of about 0.4 ns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation